Effect of oxalic acid and sulphuric acid hydrolysis on the preparation and properties of pineapple pomace derived cellulose nanofibers and nanopapers - Neenu, K. V.; Dominic, C. D. Midhun; Begum, P. M. Sabura; Parameswaranpillai, Jyotishkumar; Kanoth, Bipinbal Parambath; David, Deepthi Anna; Sajadi, S. Mohammad; Dhanyasree, P.; Ajithkumar, T. G.; Badawi, Michael (International Journal of Biological Macromolecules, 2022)
Nanocellulose is the ``green magnet'' which attracts a wide spectrum of industries towards it due to its availability, biodegradability, and possible smart applications. For the first time, pineapple pomace was being explored as an economic precursor for cellulose nanofibers. Nanofiber isolation was accomplished using a chemo-mechanical method and solution casting was adopted for the development of nanopapers. Moreover, the study examines the structural, optical, crystalline, dimensional, and thermal features of nanofibers isolated using different acid hydrolysis (oxalic acid and sulphuric acid) methods. Fourier-transform infra-red spectroscopy, 13C solid-state nuclear magnetic resonance spectroscopy, and X-ray diffraction analysis indicated the presence of type I cellulose. The transmittance, crystallinity index, and thermal stability of PPNFS (sulphuric acid treated fiber) were greater than PPNFO (oxalic acid treated fiber). The transmission electron microscopy and dynamic light scattering analysis confirmed the nanodimension of PPNFO and PPNFS. While comparing the optical and mechanical properties of nanopapers, PPNFS outperforms PPNFO. The tensile strength of the prepared nanopapers (64 MPa (PPNFO) and 68 MPa (PPNFS)) was found to be high compared to similar works reported in the literature. The prepared nanopaper is proposed to be used for food packaging applications.
Keywords: cellulose nanofibers; Cellulosic nanopapers; Pineapple pomace

Carbon black and chitin nanofibers for green tyres: preparation and property evaluation - Mathew, Mariya; Dominic, C. D. Midhun; Neenu, K. V.; Begum, P. M. Sabura; Dileep, P.; Kumar, T. G. Ajith; Sabu, Akshay Alax; Nagane, Dhiraj; Parameswaranpillai, Jyotishkumar; Badawi, Michael (Carbohydrate Polymers, 2023)
This research highlights the synergistic use of carbon black (CB) and chitin nanofibers (CHNFs) for developing green tyres for the first time. The CHNFs (12-30 nm) were prepared from chitin powder with the help of steam explosion and mild oxalic acid hydrolysis. The CHNFs were uniformly dispersed in natural rubber (NR) latex, dried, and mixed with CB in a two-roll mill to form NR/CB/CHNF composites. The NR/CB/CHNF composite at 1 phr CHNF loading exhibited tensile and tear strengths that were about 47 and 160 % greater than the NR-Neat, respectively. The dynamic mechanical analysis showed that the loss tangent (tan delta) at 60 degrees C was 50 % lower for the NR/CB/CHNF 1.0 composite than for the NR/CB50 composite. The study succeeded in developing a new green tyre tread formulation that would be helpful for attaining sustainability and a circular economy.
Keywords: carbon black; Chitin nanofibers; Green Tyre; natural rubber latex

Nanosilica from Averrhoa bilimbi juice pre-treated rice husk: preparation and characterization - Dominic, C. D. Midhun; Neenu, K. V.; Begum, P. M. Sabura; Joseph, Rani; Rosa, Derval dos Santos; Duan, Yongxin; Balan, Aiswarya; Ajithkumar, T. G.; Soumya, Mary; Shelke, Ankita; Parameswaranpillai, Jyotishkumar; Badawi, Michael (Journal of Cleaner Production, 2023)
The preparation of nanosilica from rice husk without using any concentrated mineral acids is a novel concept. This work proposes a bioleaching strategy to remove metallic impurities from rice husk for the preparation of nanosilica. Herein, nanosilica (BJRHS) was prepared by calcinating Averrhoa bilimbi juice pre-treated rice husks in a muffle furnace. The chemical and atomic structures of commercial precipitated silica (CS), rice husk ash (RHA), and BJRHS were analyzed using different analytical techniques. The optimal leaching time, calcination temperature, and calcination time were 1 h, 500 degrees C, and 6 h respectively. The particle size of BJRHS was found to be 6-12 nm, which is less than that of RHA and CS. The BET surface area of BJRHS (204 m2/g) was found to be greater than RHA (110.5 m2/g) and CS (172.1 m2/g). Mesoporous nanosilica with excellent surface area and purity was produced sustainably from rice husk which could be recommended to use in the field of catalysis, polymer technology, etc.
Keywords: Averrhoa bilimbi juice; Bioleaching; Nanosilica; rice husk

Colocasia esculenta stems for the isolation of cellulose nanofibers: a chlorine-free method for the biomass conversion - Dominic, C. D. Midhun; Maheswary, S.; Neenu, V. K.; Sajadi, S. Mohammad; Rosa, Derval dos Santos; Begum, P. M. Sabura; Mathew, Mariya; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; George, Tresa Sunitha; Resmi, V. C.; Ilyas, R. A.; et al. (Biomass Conversion and Biorefinery, 2024)
The reuse of waste products is the green key to sustainability. The extraction of cellulose nanofibers from Colocasia esculenta stems is presented in the paper. The study proved that the waste biomass could be effectively re-engineered into highly valued cellulose nanofibers (CNFs). Cellulose nanofibers were extracted via a chemo-mechanical route. The pre-treatments included mild alkali hydrolysis (2% NaOH) and chlorine-free bleaching (peroxide bleaching in an alkaline medium). Cellulose I-beta structure was confirmed using C-13 solid-state nuclear magnetic resonance spectroscopy and X-ray diffraction analysis. The elemental analysis of CNFs detected the elements, carbon and oxygen. The CNFs had a crystallinity and transmittance of 71.72% and 60%, respectively. Microscopic studies verified the elimination of non-cellulosic components and the fibrous nature of CNFs. Moreover, the fiber diameter of CNFs was 20-40 nm. Thermal analysis revealed good thermal stability of 335.8 degrees C (T-50) for nanofibers. Long-term aids are numerous in eco-friendly technology. Developing an eco-design will support zero waste ideals, lowers carbon dioxide emissions, and encourages a circular economy. Owing to the merits of natural fibers, they can be adopted in various sectors including packaging, automobile, aerospace, electronics, biomedical, construction, and furniture.
Keywords: acid hydrolysis; cellulose nanofibers; Colocasia esculenta stems; High crystallinity

Extraction, characterization, and life cycle assessment of nanosilica from millet husk: sustainable alternative with low environmental impact - Dominic, C. D. Midhun; Rosa, Derval dos Santos; Barbosa, Rennan Felix da Silva; Anagha, O. V.; Neenu, K. V.; Begum, P. M. Sabura; Kumar, V. Aswathy; Parameswaranpillai, Jyotishkumar; Siriwong, Chomsri; Ajithkumar, T. G.; Shelke, Ankita; Pasc, Andreea (Journal of Cleaner Production, 2024)
Eco-friendly approaches for silica production are highly researched to respond increasing industrial demand for bio-nanofillers. Herein, nanosilica of 10-20 nm with mesoporosity was obtained through a mild oxalic acid pre-treatment of millet husk, followed by calcination at 700 degrees C for 2 h. Compared with commercial precipitated silica (CS) and millet husk ash (MHA) directly obtained by calcination of the husk, the pre-treated silica (MHS) had higher purity, revealed using EDX spectroscopy. Moreover, FTIR and Si-29 NMR showed a higher condensation degree in MHS with 73% of Q4 siloxane bonds vs 4% in MHA. The release of the metal and organic impurities from the husk also allows to reduce the crystallinity of MHS, and to increase the specific surface area from 82 m(2)/g in MHA to 238 m(2)/g in MHS. The type II N-2 adsorption-desorption isotherms of MHA and MHS indicate aggregates of non-porous silica particles. MHS also demonstrated remarkable thermal resilience. According to the LCA analysis, MHS has a 40% lower impact on global warming, a 38% lower impact on human carcinogenic toxicity, and a 38% lower impact on terrestrial acidification compared to rice husk nanosilica. This research thus addresses sustainability challenges by repurposing millet husks, which are readily available due to continuous millet cultivation, particularly in India. By reducing the ecological impact of husk disposal through burning, this study offers an economically viable technology for high-purity silica production, aligning with global efforts to combat climate change and promote sustainable practices.
Keywords: Life cycle assessment; Millet husk; Nanosilica; Oxalic acid

Extraction of highly crystalline and thermally stable cellulose nanofiber from Heliconia psittacorum L.f. leaves - Paul, Sharon; Joseph, Anto; Hridhya, P. D.; Badawi, Michael; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Asrofi, Mochamad; Dominic, C. D. Midhun (International Journal of Biological Macromolecules, 2025)
Extracting cellulose nanofibers (CNF) from agro-waste is one of the promising and practical ways to develop sustainable nanocomposites. In this study, cellulose nanofibers were extracted from the leaves of Heliconia psittacorum for the first time. The combination of oxalic acid hydrolysis (5 wt%) and steam explosion was used for the isolation of CNF from the leaves of Heliconia psittacorum. The structural and chemical features of the prepared CNF were analyzed using various techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Solid state 13C Nuclear Magnetic Resonance Spectroscopy (13C NMR), Scanning Electron Microscopy (SEM), Energy Dispersive X ray analysis (EDX), Transmission electron Microscopy (TEM), X-Ray Diffraction (XRD) and Thermogravimetric analysis (TGA). TEM micrographs reported 15 to 40 nm diameter for the nanofibers synthesized. XRD analysis reported 91 % crystallinity index for CNF, whereas that of the untreated sample was 76 %. The maximum degradation of the CNF is reported at 355 degrees C, exceeds the untreated sample (316 degrees C). The tensile strength of the CNF derived paper was found to be 23 MPa. The recovered nanocellulose can be further utilized for various applications such as the automobile industry for developing lightweight parts, biosensors, super capacitors, absorption of greenhouse gases, wastewater treatment, and packaging applications.
Keywords: biomass valorization; Nanocellulose; Waste to resource

Sustainable cellulose nanofiber extraction from Borassus flabellifer: a comprehensive study and analytical insights - Surya, S.; Soman, Arathy; Krishnan, Akhil; Suresh, M. Parvana; Neenu, K. V.; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Begum, P. M. Sabura; Dominic, C. D. Midhun (Biomass Conversion and Biorefinery, 2025)
Cellulose, a biodegradable and renewable material, is versatile and transforms various fields. This work uses a chemo-mechanical method to discuss the extraction and analysis of palmyra (Borassus flabellifer) fruit derived cellulose nanofibers (PFCNF). The mild acid treatment, steam explosion, and homogenization could increase the physico-chemical properties of Borassus flabellifer fiber. The chemical composition and FTIR analysis confirmed the successful elimination of the hemicellulose, lignin, and other extractives in the palmyra fruit pulp. The solid-state 13C NMR proved the cellulose type I structure of the extracted PFCNF. The crystallinity index of PFCNF was found to be 57%. The yield of the cellulose was calculated to be 44%. PFCNF exhibited fibrous morphology with a nanodimension of 10-80 nm, validated using scanning electron microscopy and transmission electron microscopy. With progressive treatments, the thermal stability was increased, and the Tmax of PFCNF was 32 degrees C higher compared to the raw fibers. These superior properties further support their potential in eco-friendly packaging, advanced composites, biomedical materials, film production, electronics, coating materials, and paper production.
Keywords: Borassus flabellifer; Biomass; Cellulose nanofiber; Eco-friendly extraction; Sustainable materials; Waste valorization

Sustainable isolation of cellulose nanofibers with superior crystallinity and thermal stability from Terminalia catappa L. fruit peel waste - Harsha, R.; Mol, A. P. Princy; Paul, Sharon; Badawi, Michael; Ajithkumar, T. G.; Rao, H. Jeevan; Parameswaranpillai, Jyotishkumar; Nair, Ajalesh B.; Begum, P. M. Sabura; Dominic, C. D. Midhun (Biomass Conversion and Biorefinery, 2025)
Turning agricultural waste into value-added products is a key focus of sustainable development. Herein, cellulose nanofibers (CNF) were extracted from the pericarp of Terminalia catappa L. for the first time. The CNF was extracted by chlorine-free pretreatment methods followed by oxalic acid hydrolysis (5 wt%) assisted with steam explosion. The prepared CNF were characterized by Fourier transform infrared spectroscopy (FTIR), solid-state 13C nuclear magnetic resonance spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and thermogravimetric analysis (TGA and DTG). FTIR analysis confirmed the successful removal of lignin and hemicellulose during chemical treatment which was again validated by solid-state 13C NMR analysis. TEM image revealed that the diameter of the extracted nanofibers ranges from 14 to 18 nm. From XRD analysis, the crystallinity index of the CNF was 82%, while that of the raw sample was 62 %. The temperature at which the maximum degradation (Tmax) of CNF occurred was found to be 372 degrees C which is superior to that of the raw sample (334 degrees C). The extracted cellulose nanofibers were used to prepare cellulose paper, demonstrating a tensile strength of 1.1 MPa, indicating its potential suitability for biodegradable packaging applications.
Keywords: cellulose; Cellulose nanofiber; green synthesis; Waste to wealth

Sustainable nanocellulose extraction from salacca zalacca peel using chlorine-free and low-acid treatments - Krishnan, Akhil; Paul, Sharon; Phiri, Resego; Srisuk, Rapeeporn; Kumar Singh, Manoj; Palaniappan, Sathish Kumar; Rangappa, Sanjay Mavinkere; Dominic, C. D. Midhun; Ajithkumar, Thalasseril G.; Siengchin, Suchart (ACS Omega, 2026)
Conversion of agro-waste to value-added products is one of the important principles of a green circular economy. A novel sustainable technique has been reported by using chlorine-free extraction of cellulose nanofibers (CNFs) from the peels of Salacca zalacca, a common fruit found in Asia. The fruit peels were exposed to alkali treatment using 2% NaOH (60 degrees C, 2 h), chlorine-free bleaching using 15% hydrogen peroxide (60 degrees C, 2 h), and sulfuric acid hydrolysis (15% v/v) for the extraction of CNFs. Various analytical methods were employed to characterize the prepared CNFs. The Fourier transform infrared spectroscopy (FTIR) and 13C solid state nuclear magnetic resonance (NMR) spectra showed the complete elimination of lignin and hemicellulose in the prepared CNFs. The elemental composition and high purity of CNFs were further verified by energy-dispersive X-ray analysis (EDX). The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images proved the fibrous morphology of the prepared CNFs, and the diameters of the cellulose nanofibers were found to be 15-30 nm. The X-ray diffraction (XRD) studies disclosed the type-I cellulosic structure in the prepared CNFs with a high crystallinity index (73%). The thermogravimetric analysis (TGA) demonstrated the superior thermal stability of the prepared CNFs (T max is 350 degrees C) compared to the raw fiber (T max is 320 degrees C). Based on the obtained results, it has been explored that the extracted highly pure CNFs can be used for fabricating bionanocomposites for high performance applications, including food packaging, sensors, water treatment, green tires, etc.

Upcycling used lottery tickets: extraction, characterization, and life cycle assessment of cellulose nanofibers using a cradle-to-gate approach - Madhu, Athulya K.; Rosa, Derval Santos; de Oliveira, Sueli Aparecida; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; Badawi, Michael; Dominic, C. D. Midhun (Materials Chemistry and Physics, 2026)
This work examines a sustainable approach for the isolation, characterization and Life Cycle Impact Assessment of cellulose nanofibers derived from post-consumer lottery tickets. The lottery tickets were subjected to bleaching using 15% H2O2 and 10% NaOH in a 5:1 ratio at 80 degrees C, followed by acid hydrolysis using 5% oxalic acid assisted with steam explosion. The isolated cellulose nanofibers were 16 to 36 nm diameter range with a crystallinity index of 84.5%. The zeta potential value of-25.19 mV revealed moderate colloidal stability for nanocellulose suspension. The thermal stability of nanocellulose fibers was reported around 300 degrees C in N2 atmosphere. The films fabricated from the nanocellulose fibers reported a tensile strength of 4.6 +/- 0.90 MPa. The cradle-to-gate Life Cycle Impact Assessment revealed the impact of electricity consumption and bleaching process on the isolation of nanocellulose from waste lottery paper. These findings underline the potential of waste-derived CNFs for sus-tainable applications such as biodegradable packaging while promoting circular economy principles and green nanotechnology through waste valorisation, eco-friendly chemistry, and life cycle sustainability.
Keywords: Cellulose nanofibers (CNFs); Life cycle impact assessment; Lottery tickets; Waste to wealth